2018
DOI: 10.1111/ctr.13443
|View full text |Cite
|
Sign up to set email alerts
|

The fat mass and obesity related gene polymorphism influences the risk of rejection in heart transplant patients

Abstract: Heart transplantation is a relatively common treatment for end‐stage heart failure. The major complication of heart transplantation is organ rejection. Epigenetic could play a role in the pathogenesis of organ rejection, and the FTO gene is a mediator of DNA methylation. We analyzed a tagging FTO SNP rs17817449 in both donor and recipient DNA obtained through 370 heart transplantations. Recipient FTO genotypes were not associated with either type of rejection or with the general increase in the risk of rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(26 reference statements)
0
6
0
Order By: Relevance
“… 16 It is also reported that patients with the FTO TT genotype (SNP rs17817449) exhibits a significantly increased risk for organ rejection when undergoing heart transplantation due to end-stage heart failure. 128 FTO demethylates cardiac contractile genes such as SERCA2A, MYH6/7, RYR2 in a m6A dependent manner , and increases their protein expression to enhance cardiac contraction. 16 Moreover, overexpression of FTO is capable of reversing cardiac fibrosis and inducing angiogenesis in the heart failure post MI.…”
Section: Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“… 16 It is also reported that patients with the FTO TT genotype (SNP rs17817449) exhibits a significantly increased risk for organ rejection when undergoing heart transplantation due to end-stage heart failure. 128 FTO demethylates cardiac contractile genes such as SERCA2A, MYH6/7, RYR2 in a m6A dependent manner , and increases their protein expression to enhance cardiac contraction. 16 Moreover, overexpression of FTO is capable of reversing cardiac fibrosis and inducing angiogenesis in the heart failure post MI.…”
Section: Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“…Patients with chronic irreversible renal failure were contraindicated for orthotopic heart transplantation (OHT). Aortic biopsies of patients undergoing OHT were collected from January 2005 to December 2015 at the Institute for Clinical and Experimental Medicine in Prague as we described previously [ 22 , 23 ]. Briefly, aortic samples from 383 heart recipients (age 50.7 ± 11.9 years) and paired corresponding donors (age 38.7 ± 12.0 years) were obtained during OHT.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, FTO polymorphisms are involved in or even act as independent risk factors for CVDs, including FTO rs9939609 (T > A), FTO rs17817449, FTO rs1421085, or FTO rs1121980 (Äijälä et al, 2015; Gustavsson et al, 2014; Hubacek et al, 2018).…”
Section: “Erasers” In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%